Inhibition of Orexin/Hypocretin Neurons Ameliorates Elevated Physical Activity and Energy Expenditure in the A53T Mouse Model of Parkinson’s Disease - Stanojlovic, Milos (Int J Mol Sci, 2021)
Aside from the classical motor symptoms, Parkinson’s disease also has various non-classical symptoms. Interestingly, orexin neurons, involved in the regulation of exploratory locomotion, spontaneous physical activity, and energy expenditure, are affected in Parkinson’s. In this study, we hypothesized that Parkinson’s-disease-associated pathology affects orexin neurons and therefore impairs functions they regulate. To test this, we used a transgenic animal model of Parkinson’s, the A53T mouse. We measured body composition, exploratory locomotion, spontaneous physical activity, and energy expenditure. Further, we assessed alpha-synuclein accumulation, inflammation, and astrogliosis. Finally, we hypothesized that chemogenetic inhibition of orexin neurons would ameliorate observed impairments in the A53T mice. We showed that aging in A53T mice was accompanied by reductions in fat mass and increases in exploratory locomotion, spontaneous physical activity, and energy expenditure. We detected the presence of alpha-synuclein accumulations in orexin neurons, increased astrogliosis, and microglial activation. Moreover, loss of inhibitory pre-synaptic terminals and a reduced number of orexin cells were observed in A53T mice. As hypothesized, this chemogenetic intervention mitigated the behavioral disturbances induced by Parkinson’s disease pathology. This study implicates the involvement of orexin in early Parkinson’s-disease-associated impairment of hypothalamic-regulated physiological functions and highlights the importance of orexin neurons in Parkinson’s disease symptomology.